Prevalence of Streptococcus mitis in the bacterial plaques associated with gingivitis and its sensitivity to β-lactam antibiotics - M Azadeh; R Kasra Kermanshahi; p Ghalaiani; MR Zargarzadeh (Isfahan University of Medical Sciences, 2010)
Introduction: Bacterial plaque is the most common etiology of oral conditions such as dental caries, gingivitis and periodontal disease. One of the most common periodontal diseases is gingivitis. Elimination of bacterial plaque is the main goal in treatment of this destructive inflammatory disease. The purpose of this study was to investigate the prevalence of Streptococcus mitis in bacterial plaque and its sensitivity to β-lactam antibiotics.Materials and Methods: In this cross sectional study, we evaluated the effectiveness of 10 β-lactam antibiotics for the treatment of gingivitis via determining the antimicrobial susceptibility of the major pathogens. This study included 100 patients referring to Oral Disease Department at the School of Densitry, Isfahan University of Medical Sciences, from 2003 to 2004. Sampling of plaques on the cervical region of anterior teeth was performed with periodontal probes. Samples were then cultured into chocolate and blood agar media. In this study a total of 361 types of bacteria were isolated. Isolated strains were identified through biochemical tests. The antimicrobial susceptibility of Streptococcus mitis to 10 β-lactam antibiotics was assessed by Disk plate and Kerby- Bauer. The collected data were analyzed via t-test on a computer using SPSS (α = 0.05).Results: The results showed that there were 204 Streptococcus strains (55.9%). Streptococcus mitis formed 12.93%. The sensitivity of Streptococcus mitis to β-lactam antibiotics was more than 80% except for penicillin and ampicillin. As much as 2% of strains were sensitive to clindamycin.Conclusion: Streptococcus mitis in the dental plaques seem to be sensitive to β-lactam antibiotics. Therefore such antibiotics might be considered for the treatment of gingivitis. Key words: Gingivitis, Streptococcus mitis, β-lactam antibiotics.